How to Publish Manuscript Using Quick Submit in Open Journal System (OJS) 2.0 For Editor - Dwi Novia Al Husaeni; Dwi Fitria Al Husaeni; Asep Bayu Dani Nandiyanto; Rina Maryanti (Indonesian Journal of Multidiciplinary Research, 2022)
The purpose of this study is to show a step-by-step process for publishing journal articles using the Quick Submit Plugin in the Open Journal System (OJS) 2.0. The method used in this study is to practice directly step by step publishing articles using the Quick Submit Plugin and conducting a literature review of existing works. An example of a journal used in the quick submit practice process is the Journal of Assessment and Intervention of Children with Special Needs (JASSI Anakku). We found that publishing journal articles can use one of the plugins in OJS 2.0 namely Quick Submit Plugin. With the completion of this research, it is hoped that it can help journal managers in submitting articles through the Quick Submit Plugin in OJS 2.0.